Efeitos do PRP associado ou não ao osso autógeno particulado no reparo de cavidades ósseas em cães - Nunes Filho, Djalma Pereira [UNESP] (2003)
The purpose of the present study was to evaluate histologically the platelet rich plasma (PRP) associated or not to the autogenous bone in the mandibular bone cavities repair in dogs. For the development of the study, 6 mandibular bone cavities were performed in 4 indefinite race dogs under general anaesthesia. Three groups were created: control (filled with blood clot); PRP (filled with PRP gel); and PRP associated to the particulated autogenous bone. After 120 days, the animals were killed and the embedded parts were longitudinally and transverselly sectioned and completed through the hematoxylin and eosin method. The results showed that in the cavities filled with PRP gel the connective tissue could be seen in the middle of the lodge in all of the animals, while in the group of PRP associated to autogenous bone the cavity was totally filled with new bone. The remnant autogenous bone particles in the cavity were incorporated to the new bone or suggested being partially resorbed. Consequently, it was possible to conclude, through the experimental conditions of this study, that the PRP gel did not promote the cavity repair while in the group of PRP associated to particulated autogenous bone the repair was complete